The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1248/bpb.28.1748
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nonylphenol and Triclosan on Production of Plasma Vitellogenin and Testosterone in Male South African Clawed Frogs (Xenopus laevis)

Abstract: Recently, a number of studies have been performed worldwide to examine endocrine-disrupting chemicals (EDCs) and their interactions with the development and function of various systems in animals and humans.1-3) Among these EDCs, alkylphenol polyethoxylate non-ionic surfactants are used in the manufacture of cleaning agents, cosmetics and food products, as well as in plastic polymerization processes. Nonylphenol ethoxylates have predominantly been used, amounting to about 80% of the production of alkylphenol s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(27 citation statements)
references
References 27 publications
2
24
1
Order By: Relevance
“…No obvious changes in the sex ratio or sexually dimorphic fin traits were found in the TCS-treated group, although the lack of estrogenic effects in this study was possibly due to a relatively lower dosage (Foran et al, 2000). However, in another study on male Xenopus laevis, exposure to TCS (4e400 mg/g body weight, 14 days) lowered the plasma Vtg and testosterone levels, indicating antiestrogenic effects (Matsumura et al, 2005).…”
Section: In Vivo Studies Among Aquatic Speciescontrasting
confidence: 60%
“…No obvious changes in the sex ratio or sexually dimorphic fin traits were found in the TCS-treated group, although the lack of estrogenic effects in this study was possibly due to a relatively lower dosage (Foran et al, 2000). However, in another study on male Xenopus laevis, exposure to TCS (4e400 mg/g body weight, 14 days) lowered the plasma Vtg and testosterone levels, indicating antiestrogenic effects (Matsumura et al, 2005).…”
Section: In Vivo Studies Among Aquatic Speciescontrasting
confidence: 60%
“…This level of induction (1 ng/ml) is similar to physiological levels seen in female LMB during active reproduction and corresponds to peak levels observed in this species during the annual reproductive cycle. Although NP has been shown to interact directly with the ERs of numerous species (White et al 1994, Kuiper et al 1998, Balaguer et al 1999, Nishikawa et al 1999, Gale et al 2004), a few reports have suggested that the estrogenic effects of NP in vivo are the result from altered levels of endogenous steroids (Acevedo et al 2005, Matsumura et al 2005, Soverchia et al 2005. Exposure of fathead minnows to NP also resulted in increased levels of plasma E 2 with a concomitant decrease in testosterone (Soverchia et al 2005).…”
Section: Regulation Of Lmb Er Isotype and Vtg1 Expression By Np In Vivomentioning
confidence: 99%
“…Further studies demonstrated that TCS might exhibit weak estrogenic activity because concentrations of hepatic vitellogenin were increased in male medaka fry exposed to 20 lg/l and 100 lg/l TCS (Ishibashi et al 2004) and in mature male western mosquitofish (Gambusia affinis) treated with TCS at 101.3 lg/l TCS in laboratory exposure experiments (Raut and Angus 2010). However, male South African clawed frogs (Xenopus laevis) injected with 4, 40, or 400 lg/g TCS (per body weight) exhibited decreased plasma vitellogenin and testosterone levels, suggesting that TCS may possess estrogen-antagonist activity (Matsumura et al 2005). In vitro studies also confirmed that TCS possesses both estrogenic and androgenic activity in assays with breast cancer cells ) and receptor-based bioassay screens (Ahn et al 2008).…”
mentioning
confidence: 99%